Does experience of banking crises affect trust in banks? - Zuzana Fungáčová; Eeva Kerola; Laurent Weill (Bank of Finland, Institute for Economies in Transition (BOFIT), 2019)
This paper investigates how past experience with banking crises influences an individual's trust in banks. We combine data on banking crises for the period 1970–2014 with individual data on trust in banks for 52 countries. We find that experiencing a banking crisis diminishes a person's trust in banks, and that high exposure to banking crises is negatively related to trust in banks. An individual's age at the time of the crisis is important, and significant for individuals between 41 and 60 years of age at the time of the banking crisis. Both severe and mild crises diminish trust in banks, but a severe banking crisis hits also young people's trust, while less severe banking crises mainly degrade trust of more mature people. The detrimental effect for trust in banks seems to be connected specifically to systemic banking crises. Other types of financial crises incur a less significant effect. Overall, our results indicate that banking crises generate previously unrecognized costs for the economy in the form of a lasting reduction of trust in banks.
URN:NBN:fi:bof-201910291542
Keywords: G21; O16; 330